Entrepreneurial attitude and entrepreneurial efficacy of technical secondary school students - Lope Pihie, Zaidatol Akmaliah; Bagheri, Afsaneh (The Vocational Aspect of Education, 2010)
Entrepreneurial attitude and entrepreneurial efficacy are considered to be two important factors influencing students’ intention and success in becoming entrepreneurs. This study was conducted to determine the entrepreneurial attitude and entrepreneurial efficacy of 3000 students following technical subjects in the secondary schools of Malaysia. The findings indicate that students scored high on entrepreneurial attitude components including self‐esteem cognition, achievement cognition, and achievement affect. However, students’ mean score for entrepreneurial self‐efficacy is moderate to high. This paper also discusses the importance of intervention programs and proper teaching and learning strategies to improve technical students’ entrepreneurial attitude and self‐efficacy.